Real Time River Bridge Monitoring and Alert System using GSM - Sawardekar, Sameep S; Nalbalwar, Sanjay; SB, Deosarkar; Singh, Sachin (International Journal of Computer Sciences and Engineering, 2019)
In India, many bridges built by the British east India company 100 years ago. Due to long time span, it is required to monitor them. The main objective of the proposed system is to read the water level and vibration of the bridge continuously. Upon crossing the threshold level, a short message get send to the observation section periodically by using GSM (Global System for mobile communication).This system may help in flood situation and may be a communication tool between the traveler and government. This proposed system also avoids the traffic jam due to availability of time with users for finding an alternative solution before they are going to be stuck at flood.